PENGARUH KOMPETENSI DAN KEPRIBADIAN TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN GURU - Fathoni, 11.52.02.0048 (Students Journal of Economic and Management, 2013)
The purpose of this research was analyze the enfluence of teachersâ competence and personality towards teacher performance through mediation of teachersâ commitment. The populationÂ  of this research were 212 teachers and the samples were 139 teachersÂ  of Government Yunior High School in Pati Regency, Juwana District. Data was gathered by giving questionnaire to the respondent using a samples method. The research proved that the ability of model to explain the influence of teachersâ competence and personality toward teacherâ commitment was 66,7 % , while to explain the enfluence of the tree variables all together toward teacherâs performance was 61,9 %. For data operation, SPSS 16.0 version was used. The result are the first hypothesis (H1) âTeacher Competence has positive and significant effect on Teachersâ Commitment means that higher influence ofÂ  Competence , will make higher of it (H2) âPersonalityÂ  has a positive and significant effect on Teachersâ Commitment means that higher influence ofÂ  personality, will make higher of it. In the third hypothesis (H3) â Teachers Competence has positive and significant impact on teachers performance, means that the higher influence of it, the higher performance causedâ Fourth hypothesis (H4) âPersonality has positive and significant effect on prerformance of teacher means the higher the of it will improve teacher performance. The Fifth hypothesis (H5) Teachersâ Commitment has positive influence on performance means that the higher it will have influence the higher performance caused.Â  The Sixth hypothesis (H6) Teachersâ CommitmentÂ  has not positiveÂ  mediated influence competence toward teacher performance. (H7) Teachersâ CommitmentÂ  has not positive mediated influence personality toward teacher performance. Â  Keyword : teacher competencies, personality, teacher commitment and teacher performance